Faith & Fitness in Farming Families - Moore, Mallory (My University, 2021)
Although agriculture is a leading industry in North Carolina, farmers and farmworkers are one of the most underserved populations in the state due to rural health disparities. The Faith & Fitness in Farming Families Doctor of Nursing Practice (DNP) project’s primary purpose was to increase health education and improve self-efficacy in personal health and wellness for individuals who live, work, play, and pray in farm communities. The project addressed pertinent health initiatives to a rural, farming population in eastern North Carolina through primary and secondary intervention tools. Through the utilization of the RE-AIM framework, a faith-centered tool was created and implemented to empower participants to self-screen for conditions and self-refer for care as the means to reduce harm from preventable and manageable conditions. Following the creation of a health-focused Bible study curriculum, a 6-week, small group study was held at a rural Methodist church in eastern North Carolina. An average of 10.17 adults participated in the Bible study and provided positive evaluation of the program through Likert surveys and additional comments. Community-based health initiatives, such as this DNP project, allow health care providers to better understand their patients’ lives and hardships, and seek ways to break through possible barriers to care. The more improvements in overall wellbeing, the less need there will be for secondary and tertiary interventions, and less strain there will be on the healthcare system.
Keywords: rural, farming, health disparities, primary care, community-based, faith-based